The religious history of American women : reimagining the past - Brekus, Catherine A. (The University of North Carolina Press, 2007)
More than a generation after the rise of women's history alongside the feminist movement, it is still difficult, observes the author of this book, to locate women in histories of American religion. In this collection, contributors explore how considering the religious history of American women can transform our dominant historical narratives. Covering a variety of topics the book enhances our understanding of both religious history and women's history.